The Effect of Tong-Xie-Yao-Fang on Intestinal Mucosal Mast Cells in Postinfectious Irritable Bowel Syndrome Rats - Ma, Xiangxue (Evid Based Complement Alternat Med, 2017)
Objective. To investigate the effects of Tong-Xie-Yao-Fang (TXYF) on intestinal mucosal mast cells in rats with postinfectious irritable bowel syndrome (PI-IBS). Design. PI-IBS rat models were established using a multistimulation paradigm. Then, rats were treated with TXYF intragastrically at doses of 2.5, 5.0, and 10.0 g·kg(−1)·d(−1) for 14 days, respectively. Intestinal sensitivity was assessed based on abdominal withdrawal reflex (AWR) scores and fecal water content (FWC). Mast cell counts and the immunofluorescence of tryptase and c-Fos in intestinal mucosa were measured; and serum IL-1β, TNF-α, and histamine levels were determined. Results. AWR reactivity and FWC which were significantly increased could be observed in PI-IBS rats. Remarkably increased mast cell activation ratio in intestinal mucosa, together with increased serum TNF-α and histamine levels, could also be seen in PI-IBS rats; furthermore, PI-IBS-induced changes in mast cell activation and level of serum TNF-α and histamine could be reversed by TXYF treatment. Meanwhile, tryptase and c-Fos expression were also downregulated. Conclusion. TXYF improves PI-IBS symptoms by alleviating behavioral hyperalgesia and antidiarrhea, the underlying mechanism of which involves the inhibitory effects of TXYF on activating mucosal mast cells, downregulating tryptase and c-Fos expression, and reducing serum TNF-α and histamine levels.